DYNAMICS OF PERCEPTION OF VALUES OF KRASNOYARSK YOUTH (2008-2013) - V. I. Zlotkovsky (Science and Innovation Center Publishing House, 2014)
In this article, basing on the results of monitoring researches (2008-2013) of  life aspirations of Krasnoyarsk young people, the factors which help achieve these purposes and expectancy of future location of residence after graduation from institutions are analyzed. It is established that young men mainly wish to become businessmen, directors and top-managers, and young women want to be their wives or work as the actresses or models. And the youngsters are hardly interested in professions of engineers, managers, teachers, doctors, scientists. Achievement of their purposes in life pupils of high schools generally connect to good education and high personal qualities. Upon transition to higher educational institutions, they start hoping generally in touch and acquaintances. It is revealed that less than a half of seniors students of high schools of the city, given the choice, would like to live after their graduation in Krasnoyarsk. Growing up young peoples’ desire to leave the city grows. The students who are studying as engineers, agricultural workers and artists are more inclined to these moods. Purpose: to receive indirect information on readiness of Krasnoyarsk youths to participate in innovative development of the region. Methods: questionnaire. In April-May, 2008 579 students of day form of education of four higher education institutions of the city, 782 students of 19 high schools of the city are interrogated [1, page 61-66]. In December, 2013 903 students of day form of education of seven higher education institutions are interrogated. During the forming and realization of the selection of students their presence at different courses and profiles of education they were getting were taken into account. Results. The data obtained during monitoring researches doesn't give a definite answer to the question about readiness of young people to participate in innovative development of the region. The conclusion about the need for a special chapter about the youth policy within the program of social and economic development of Krasnoyarsk Territory is drawn.